2021
DOI: 10.3171/2020.7.jns201174
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of radial versus femoral artery access for acute stroke interventions

Abstract: OBJECTIVEIn this study, the authors aimed to investigate procedural and clinical outcomes between radial and femoral artery access in patients undergoing thrombectomy for acute stroke.METHODSThe authors conducted a single-institution retrospective analysis of 104 patients who underwent mechanical thrombectomy, 52 via transradial access and 52 via traditional transfemoral access. They analyzed various procedural and clinical metrics between the two patient cohorts.RESULTSThere was no difference between patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…In conclusion, the present findings indicate that TRA is not inferior to TFA in the probability and times of catheterization and revascularization as well as other clinical outcomes for mechanical thrombectomy in acute stroke. Our data confirm the feasibility and effectiveness of the TRA in thrombectomy for acute stroke with similar outcomes compared with TFA, as recently reported in other series [47]. With increasing experience using TRA, this approach can be used as the first option, as an alternative in difficult anatomies on CTA, and as a second option, but it is recommended to have passed the learning curve and to avoid the humeral access associated with a higher rate of complications.…”
Section: Discussionsupporting
confidence: 88%
“…In conclusion, the present findings indicate that TRA is not inferior to TFA in the probability and times of catheterization and revascularization as well as other clinical outcomes for mechanical thrombectomy in acute stroke. Our data confirm the feasibility and effectiveness of the TRA in thrombectomy for acute stroke with similar outcomes compared with TFA, as recently reported in other series [47]. With increasing experience using TRA, this approach can be used as the first option, as an alternative in difficult anatomies on CTA, and as a second option, but it is recommended to have passed the learning curve and to avoid the humeral access associated with a higher rate of complications.…”
Section: Discussionsupporting
confidence: 88%
“…There were two (0.67%) reported access-site complications among the transradial group, whereas there were 27 (5.8%) in the transfemoral group. The frequency of symptomatic ICH reported in three studies [13][14][15] and our case series was 4.78% in the transradial group and 8.06% in the transfemoral group. Successful reperfusion was achieved in 88.8% of the transradial group and 93.2% of the transfemoral…”
Section: Transradial Versus Transfemoral Analysissupporting
confidence: 41%
“…Most patients were treated for an anterior large vessel occlusion (90.4% of the transradial group, 95.1% of the transfemoral group). In addition to our case series, only Khanna et al 14 presented the frequency of each thrombectomy technique. Only two studies reported on the use of BGCs.…”
Section: Transradial Versus Transfemoral Analysismentioning
confidence: 91%
“… 31 In both approaches, similar vascular characteristics are associated with revascularization success and increased procedural duration. 32 In addition, patients with specific characteristics, especially difficult arch anatomy, might be better treated with a transradial approach, 33 , 34 but this requires further research.…”
Section: Discussionmentioning
confidence: 99%